Formal Verification of Programs in Functional Dataflow Parallel Language - M. S. Kropacheva; A. I. Legalov (Моделирование и анализ информационных систем)
The article is devoted to the methods of proving parallel programs correctness that are based on the axiomatic approach. Formal system for functional data-flow parallel programming language Pifagor is described. On the basis of this system programs correctness could be proved.